The Application of Christian Religious Education Through Dinner Table Culture: An Analysis of Internalization and Spiritual Dialectics in Sentani Family - Labobar, Yohanes Kristian; Kopeuw, Philipus M. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the application of Christian Religious Education (CRE) through the culture of